The impact of oral health on the quality of life of nursing home residents - Porter, Jessie (Health Qual Life Outcomes, 2015)
BACKGROUND: Good oral health in older residents of nursing homes is important for general health and quality of life. Very few studies have assessed how oral symptoms affect residents’ quality of life. OBJECTIVE: To assess the clinical and subjective oral health, including oral health related quality of life (OHRQoL), and the association of oral symptoms with OHRQoL in older people residing in nursing homes in Islington, London. METHOD: Overall, 325 residents from nine nursing homes were clinically examined and 180 residents were interviewed to assess their oral symptoms and their OHRQoL using the OIDP measure. Managers and carers working in the homes were also interviewed. RESULTS: Almost two thirds of the sample were dentate (64.5 %). 61.3 % of dentate and 50.9 % of edentate residents reported problems such as dry mouth, sore cracked lips, broken teeth and toothache and ill-fitting dentures. Oral health impacted considerably upon resident’s OHRQoL; 20.2 % of dentate and 30.9 % of edentate reported at least one oral impact in the past 6 months. Sensitive teeth, toothache, bleeding gums, dry mouth and loose natural teeth among the dentate and loose or ill-fitting dentures among the edentate were strongly associated with higher prevalence of oral impacts even after adjusting for demographic and socio-economic factors, and for the number of teeth (dentate only). CONCLUSION: The burden of oral conditions was considerable. Oral symptoms were very common and were strongly associated with residents’ worse OHRQoL. Health promotion programmes are important to help residents maintain an acceptable level of oral health and function.